Policy Transformation for Tahura R. Soerjo Conservation Awareness: ISBN 978-630-95064-6-7 - Hamid, Abdul (Technium Books, 2025)
The book: Policy Transformation for Tahura R. Soerjo Conservation Awareness Authors: Abdul Hamid, Andjar Prasetyo, Tri Weda Raharjo, Amir HT, Teguh Prayitno, Eka Prabawati, Mohammad Sofyan Budiarto, Yudiyanto Tri Kurniawan, Firman Syah Ali, Suharyon, Hasim Ashari, Linda Wige Ningrum, Gatot Kustyadji, Endriana Wahyu Alita, Ari Sasmoko Adi, Fitriyatus Sholihah Editor: Amodu, Salisu Ameh PhD Engr. Imran Arshad ISBN: 978-630-95064-6-7 is published in Technium.